Bearing-Only Measurement Self-Localization, Velocity Consensus and Formation Control - Ye, Mengbin; Anderson, B.D.O.; Yu, C. (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2017)
Self-localization and formation control tasks are considered when each agent in a multiagent formation observes its neighbors but does not communicate. Each agent is restricted to a predefined motion type on a 2-D plane and collects bearing-only measurements over a time interval to localize neighboring agents. The localization process is used by a three agent formation to achieve velocity consensus combined with formation shape control. Simulations are provided and noisy bearing measurements are investigated.